Rate of increase and current abundance of humpback whales in West Greenland - Heide-Jørgensen, M. P.; Laidre, K. L.; Hansen, R. G.; Burt , M. L.; Simon , M.; Borchers , D. L.; Hansen, J.; Harding , K.; Rasmussen, M.; Dietz, R.; Teilmann, J. (J. Cetacean Res. Manage., 2023)
Aerial line transect surveys of the density of humpback whales (Megaptera novaeangliae) conducted off West Greenland eight times between 1984 and 2007 were used to estimate the rate of increase on the summer feeding ground. Only surveys in 1993, 2005 and 2007 had enough sightings to construct independent density estimates, whereas the surveys in 1984–85 and 1987–89 had to be merged and treated as two surveys. The annual rate of increase was 9.4% yr–1 (SE = 0.01) between 1984 and 2007. This rate of increase is higher than the increase estimated at the breeding grounds in the West Indies, but is of the same magnitude as the observed rate of increase at other feeding grounds in the North Atlantic. A matrix model based on observed life history parameters revealed that the theoretical growth rate of a humpback whale population ranged between 1 and 11%. This confirms that the observed growth in West Greenland is within the plausible values. The survey in 2007 was used to make a fully corrected abundance estimate including corrections for whales that were submerged during the passage of the survey plane. The line transect estimate for 2007 was 1,020 (CV = 0.35). When the estimate was corrected for perception bias with mark-recapture distance sampling (MRDS) methods, the abundance increased to 1,505 (0.49). A correction for availability bias was developed based on time-depth-recorder information on the time spent at the surface (0–4m). However, used directly this correction leads to a positively-biased abundance estimate and instead a correction was developed for the non-instantaneous visual sighting process in an aircraft. The resulting estimate for 2007 was 3,272 (CV = 0.50) for the MRDS analysis. An alternative strip census estimate deploying a strip width of 300m resulted in 995 (0.33) whales. Correction for perception bias resulted in 991 (0.35) whales and corrected for the same availability bias as for the MRDS method resulted in a fully corrected estimate of 2,154 (0.36) humpback whales in West Greenland in 2007.